2014
DOI: 10.1002/ijc.29164
|View full text |Cite
|
Sign up to set email alerts
|

Calcium intake and colorectal adenoma risk: Dose‐response meta‐analysis of prospective observational studies

Abstract: Evidence from randomized controlled trials suggests that calcium may protect against recurrence of colorectal adenomas, which could lead to the subsequent prevention of cancer. Yet the trials used only a large single dose and were of small sizes, and thus, knowledge of the dose-response relationship and influence on high-risk adenomas is limited. To address these issues, we conducted linear and nonlinear dose-response meta-analyses primarily based on prospective observational studies published up to July 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Study treatment ended in December 1996. Baseline serum 25‐hydroxyvitamin D concentrations were measured in 2001 on stored specimens obtained at time of enrollment using a competitive protein binding radioimmunoassay kit from Nichols Institute Diagnostics that used the vitamin D binding protein as the binding agent and H‐labeled 25‐hydroxyvitamin D as the reporter …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study treatment ended in December 1996. Baseline serum 25‐hydroxyvitamin D concentrations were measured in 2001 on stored specimens obtained at time of enrollment using a competitive protein binding radioimmunoassay kit from Nichols Institute Diagnostics that used the vitamin D binding protein as the binding agent and H‐labeled 25‐hydroxyvitamin D as the reporter …”
Section: Methodsmentioning
confidence: 99%
“…Considerable evidence from preclinical and observational studies suggests that calcium supplementation exerts a protective effect against colorectal neoplasia, both colorectal cancer and its main precursor lesion, colorectal adenomas. [1][2][3][4] We conducted two randomized, double-blind, placebo-controlled trials of calcium supplementation (1,200 mg/day elemental calcium as carbonate) for the prevention of new colorectal adenomas in individuals with a recent history of adenomas. These studies were conducted 16 years apart with disparate results.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to oral supplements, dietary calcium intake is relatively safe. Thus, many prior meta-analyses have focused on the association between dietary calcium intake and risk of colorectal cancer, breast cancer, and prostate cancer [11,12,13]. However, there is no systemic analysis carried out regarding the relationship between calcium intake and the risk of esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Among 16 observational studies (6 prospective cohort and 10 case-control studies), 15 (94%) reported inverse associations, of which 4 were statistically significant. Additionally, in a meta-analysis of 7 prospective studies, a statistically significant 13% lower risk of adenomas was reported among those in the highest relative to the lowest levels of total calcium intake (33). In the same meta-analysis, 8 additional prospective studies were pooled in a dose-response analysis in which a statistically significant 5% lower risk of adenomas per 300 mg/day increase in total calcium intake was reported.…”
Section: Discussionmentioning
confidence: 99%